2008
DOI: 10.3748/wjg.14.6339
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos overexpression increases the proliferation of human hepatocytes by stabilizing nuclear Cyclin D1

Abstract: flow cytometry showed that c-Fos accelerated the cell cycle kinetics. Following serum stimulation, Cyclin D1 was more abundantly expressed in c-Fos overexpressing cells. Cyclin D1 accumulation did not result from increased transcriptional activation, but from nuclear stabilization. Overexpression of c-Fos correlated with higher nuclear levels of inactive phosphorylated GSK-3β, a kinase involved in Cyclin D1 degradation and higher levels of EGF-R mRNA, and EGF-R protein compared to IHH-C both in serum starved, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Similar to this observation, Güller et al (37) recently reported that Fos overexpression can cause an increase in p27…”
Section: ϫ469) In the P27supporting
confidence: 77%
“…Similar to this observation, Güller et al (37) recently reported that Fos overexpression can cause an increase in p27…”
Section: ϫ469) In the P27supporting
confidence: 77%
“…The direct interaction of EWS/ATF1 at CRE may induce continuous transcriptional activation of Fos in EWS/ATF1-induced tumor cells. Previous studies have demonstrated a higher expression level of FOS to be involved in tumor growth in several cancers (42)(43)(44), and overexpression of Fos results in osteosarcoma formation in transgenic mice (45,46). Here we showed that FOS was also upregulated in CCS by the EWS/ATF1 fusion transcript and that the increased FOS promoted the growth of EWS/ATF1-related sarcomas.…”
Section: Discussionsupporting
confidence: 60%
“…c-Fos was overexpressed in some tamoxifen-resistant human breast tumors (20) and highly overexpressed in malignant oral tissues (21). It could also contribute to hepatocarcinogenesis (22). In a murine skin carcinogenesis model, c-Fos was shown to be required for malignant tumor conversion (23).…”
mentioning
confidence: 99%